Enhanced presynaptic mitochondrial energy production is required for memory formation - Erica L. Underwood; John B. Redell; Kimberly N. Hood; Mark E. Maynard; Michael Hylin; M. Neal Waxham; Jing Zhao; Anthony N. Moore; Pramod K. Dash (Scientific Reports, 2023)
Abstract Some of the prominent features of long-term memory formation include protein synthesis, gene expression, enhanced neurotransmitter release, increased excitability, and formation of new synapses. As these processes are critically dependent on mitochondrial function, we hypothesized that increased mitochondrial respiration and dynamics would play a prominent role in memory formation. To address this possibility, we measured mitochondrial oxygen consumption (OCR) in hippocampal tissue punches from trained and untrained animals. Our results show that context fear training significantly increased basal, ATP synthesis-linked, and maximal OCR in the Shaffer collateral-CA1 synaptic region, but not in the CA1 cell body layer. These changes were recapitulated in synaptosomes isolated from the hippocampi of fear-trained animals. As dynamin-related protein 1 (Drp1) plays an important role in mitochondrial fission, we examined its role in the increased mitochondrial respiration observed after fear training. Drp1 inhibitors decreased the training-associated enhancement of OCR and impaired contextual fear memory, but did not alter the number of synaptosomes containing mitochondria. Taken together, our results show context fear training increases presynaptic mitochondria respiration, and that Drp-1 mediated enhanced energy production in CA1 pre-synaptic terminals is necessary for context fear memory that does not result from an increase in the number of synaptosomes containing mitochondria or an increase in mitochondrial mass within the synaptic layer.